Development of a transmission-based open-ended coaxial-probe suitable for axillary lymph node dielectric measurements - Savazzi, M.; Porter, E.; O'Halloran, M.; Costa, J. R.; Fernandes, C. A.; Felício, J. M.; Conceição, R. (2020 14th European Conference on Antennas and Propagation (EuCAP), 2020)
We assess the feasibility of a transmission-based open-ended coaxial-probe for tissue dielectric properties estimation. The ultimate goal is to use it for axillary lymph node dielectric measurement, which is not trivial when applying the state-of-the-art reflection-based open-ended coaxial-probe. The proposed technique consists in placing the material under test between two opposite open-ended coaxial-probes and record the transmission coefficient. We numerically assess three coaxial probe configurations, in order to ensure adequate transmission and sensing volume. The final setup allows for enough propagation through a 5mm sample (which will be sufficient for the measurements of axillary lymph nodes), while confining the sensing volume to the region of interest. Experimental tests on two materials of different permittivity ranges showed good agreement between the measured and numerical transmission coefficient. Moreover, we observed that the transmission coefficient can highlight the contrast between materials with different dielectric properties. The promising initial results motivate the further application of the method to the case of axillary lymph nodes.